Encapsulation of probiotics using fluidic set-up for dysphagic patients - Ng, Clive Yi Jie (Nanyang Technological University, 2024)
Dysphagia affects an individual’s swallowing reflexes and can lead to difficulties in swallowing food. The low consumption of essential nutrients can cause gut microbiota dysbiosis, which is associated with the onset of immunological diseases. Probiotics supplementation is an effective, non-invasive treatment option for gut microbiota dysbiosis, yet there are few commercial products catered for dysphagic patients. Encapsulation of probiotics using a fluidic device can prepare gel-like probiotic particles below 2mm, which can be easily incorporated into the food of dysphagic patients. Furthermore, encapsulation can confer protective effects against thermal stress and gastric acidity. Thus, we identified two fluidics-based methods of encapsulating probiotics in this study. Multiple factors were studied to find the optimal encapsulation conditions. Our findings showed that a T-junction off-device gelation method with a dispersed phase composition of 1.5% sodium alginate and 40% glycerol, alongside a continuous phase composition of soybean oil and 0.1% Span 80, combined with a 1% CaCl2 gelation bath in a 50:500 μl/min Qd:Qc ratio was able to produce small, circular particles with a narrow Particle Size Distribution (PSD). Exposure of encapsulated L. plantarum and L. paracasei to simulated gastric fluid (SGF) significantly increased their viability compared to free probiotics. Further studies need to be done to bring the project to completion, such as co-encapsulation with polycations, taste and sensorial analysis of the encapsulated probiotics, and integration of encapsulated probiotics into food preparation processes.